Implications of eco-addition inhibitor to mitigate corrosion in reinforced steel embedded in concrete. (20th July 2019) - Anitha, Rajan; Chitra, Subramanian; Hemapriya, Venkatesan; Chung, Ill-Min; Kim, Seung-Hyun; Prabakaran, Mayakrishnan
Graphical abstract: Highlights: A cost effective inhibitor for extenuating corrosion in rebar. Rosa damascena indubitably diminishes corrosion of rebar in aggressive environment. Regression coefficient nearer to unity discloses the best fit for Langmuir adsorption. Electrochemical studies evinced the shielding effect and mixed nature of inhibitor. SEM images exposed the creation of protective layer. Abstract: The deleterious and entanglement of synthetic inhibitors provokes a platform for assessment of Rosa damascena ( R. damascena ) leaves as a green corrosion inhibitor on reinforced steel rebar. The inhibitory action was realised by electrochemical impedance spectroscopy and polarisation studies in simulated pore solution. Electrochemical measurements showed that the charge transfer resistance increases as the concentration of acid and ethanol extracts of R. damascena increases. Tafel polarisation curves divulge that the potential is shifted towards positive side evincing the nobility of the inhibitor. The experimental model for adsorption obeyed Langmuir adsorption isotherm disclosing the physisorption behaviour. The maximum protection efficiency is 82% at a concentration of 12 v/v %. SEM images stipulates the chelating effect of phytochemical constituents containing hetero atoms such as O, N, aromatic rings and π-electrons interacting with iron ions resulting in the shielding of the metal from corrosion.